BS7988 (A Code of Practice for the use of Information Technology in the Delivery of Assessments) - Time for a Review? - Christine Ward; Steve Lay; David Keech (2004)
BS 7988, A Code of Practice for the use of information technology (IT) in the delivery of assessments, was developed during 2001 and published in March 2002. The relevant BSI panel is now considering the need for a revised version. This paper invites comments on the need for revision and poses some questions for discussion.